2000
DOI: 10.1111/0022-4146.00187
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Marginal Willingness to Pay for Commuting

Abstract: With informational frictions on the labor market, hedonic wage regressions provide biased estimates of the willingness to pay for job attributes. We show that a recent theoretical result, which states that variation in job durations does provide good estimates in case of a basic on-the-job search model, can be generalized to a wide class of search models. We apply this result by estimating the marginal willingness of employed workers to pay for commuting, using Dutch longitudinal data. The average willingness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 24 publications
7
88
0
1
Order By: Relevance
“…Instead of using wage differentials to identify the value of non-wage characteristics, differential job quitting can be exploited. By observing the relative importance of differences in non-wage characteristics vis-à-vis wages in determining job leaving, it is possible to estimate workers' marginal willingness to pay (MWP) for physical working conditions (Gronberg and Reed (1994)), commuting distance (van Ommeren et al (2000)) or the remaining duration of a contract (van Ommeren and Hazans (2008)). The approach allows an estimation of MWP, a structural preference parameter, in absence of a full structural model.…”
Section: Wealth and Labour Supplymentioning
confidence: 99%
“…Instead of using wage differentials to identify the value of non-wage characteristics, differential job quitting can be exploited. By observing the relative importance of differences in non-wage characteristics vis-à-vis wages in determining job leaving, it is possible to estimate workers' marginal willingness to pay (MWP) for physical working conditions (Gronberg and Reed (1994)), commuting distance (van Ommeren et al (2000)) or the remaining duration of a contract (van Ommeren and Hazans (2008)). The approach allows an estimation of MWP, a structural preference parameter, in absence of a full structural model.…”
Section: Wealth and Labour Supplymentioning
confidence: 99%
“…Herzog and Schlottmann (1990) and Gronberg and Reed (1994) reported higher estimates for the willingness to pay to avoid jobinduced risk. Van Ommeren et al (2000) and Manning (2003) found higher estimates for the willingness to pay to avoid commuting. Similarly, Bartik et al (1992) compared the MWP for residential characteristics based on residential moving behaviour and hedonic price methods and showed that the MWP estimates for crime reduction and school quality are higher than those based on conventional estimates.…”
Section: Introductionmentioning
confidence: 95%
“…These considerations have generated a number of studies aimed at estimating the MWP for job attributes using data on job moving behaviour and comparing the MWP estimates with conventional estimates (Herzog and Schlottmann, 1990;Gronberg and Reed, 1994;Van Ommeren et al, 2000;Manning, 2003). 1 These studies point to considerably higher estimates than those based on conventional hedonic wage methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations